Enforcing Socio-Economic Rights as Individual Rights the Role of Corrective and Distributive Forms of Justice in Determining “Appropriate Relief - Mbazira, Christopher (Economic and Social Rights in South Africa, 2008)
Different notions of justice influence the remedies that courts grant in socio-economic rights litigation. The two theories of justice discussed here derive from the philosophies of corrective and distributive forms of justice.